2003
DOI: 10.1359/jbmr.2003.18.11.2010
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Treatment of Ovariectomized Sheep Affects Mineral Density, Structure, and Mechanical Properties of Cancellous Bone

Abstract: Thus far, orthopedic research lacks a suitable animal model of osteoporosis. In OVX sheep, 6 months of steroid exposure reduced bone density and mechanical competence. Bone properties and bone formation did not recover for another 6 months. Therefore, steroid-treated OVX sheep may serve as a large animal model for osteopenic bone. Introduction:The purpose of this study was to explore the effects of glucocorticoid treatment on cancellous bone density, microarchitecture, biomechanics, and formation of new bone. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
34
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 29 publications
8
34
1
Order By: Relevance
“…The parameters specifying changes of bone density (BV/TV, Tb.N, Tb.Th, Conn.Dn) and changes of porosity (Po.tot, Po.cl, Po.op, BS/BV) were determined. Similar parameters were monitored by Turner et al (1995) and Schorlemmer et al (2003). By analysing the obtained results, it can be observed that in the group of sheep treated with ovariectomy (PC) in relation to the negative control group (NC), based on the samples from the proximal femoral bone epiphyses, the group is characterised by a general increase in bone density parameters and a decrease in porosity, including total density of 15%.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…The parameters specifying changes of bone density (BV/TV, Tb.N, Tb.Th, Conn.Dn) and changes of porosity (Po.tot, Po.cl, Po.op, BS/BV) were determined. Similar parameters were monitored by Turner et al (1995) and Schorlemmer et al (2003). By analysing the obtained results, it can be observed that in the group of sheep treated with ovariectomy (PC) in relation to the negative control group (NC), based on the samples from the proximal femoral bone epiphyses, the group is characterised by a general increase in bone density parameters and a decrease in porosity, including total density of 15%.…”
Section: Resultsmentioning
confidence: 70%
“…Guided by other researchers' insights, examinations of radiological density of bones were also made in the group of sheep treated with steroidal medications (SC). Schorlemmer et al (2003) in their studies proved that treatment with steroidal medications for a long time would lead to secondary osteoporosis and would intensify changes taking place in the skeletal system. After a six-month application of glucocorticosteroids, a biopsy of tibial bones showed a decrease in bone density of 19%.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, steroid-induced ONFH in young patients directly inhibits osteoblastic bone formation and stimulates increased bone resorption [24,25]. Kindsfater et al [10] reported prosthesis survival rates up to eight years in a general group of patients with osteoarthritis, with intermediate-term clinical results of BHA being satisfactory independent of age and not related to underlying diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Bone loss has been reported previously at various skeletal sites in sheep following ovariectomy [5,16,27,28,42], chronic steroid therapy [7,10] or dietary manipulation [9], but in none of these studies, could these animals be classified as osteoporotic by standard definitions. Other studies have implemented combination treatments to induce osteoporosis in sheep [13, 14, 19-21, 29, 32, 33] and although such treatments have resulted in further bone loss compared to the single treatments, lumbar spine BMD was either not reduced significantly [13,29,32,33] or it did not achieve the minimum of 25% bone loss [20,21] required to classify them as osteoporotic. The current study was undertaken in an attempt to achieve more substantial bone loss in the lumbar spine of domestic sheep, a large animal that is frequently used for experimental studies.…”
Section: Discussionmentioning
confidence: 99%